Using roc analysis to determine the cutoff score for problematic cryptocurrency trading scale - Menteş, Nurettin; Bulut, Mahmut (Journal of Dependence, 2023)
Objective: The aim of this study is to determine the cut-off point for the Problematic Cryptocurrency Trading Scale that is used in detecting individuals who exhibit addictive and gambling-like behaviors regarding cryptocurrencies, the use of which has increased rapidly in recent years. Method: 2180 individuals participated into the study. After the exclusion of questionnaires with missing data, a dataset consisting of 2132 participants was used for the analyses. The Problematic Cryptocurrency Trading Scale was used in the study. The cut-off point for the scale was determined using the two-step cluster analysis and ROC analysis. The obtained total scale scores were categorized with the help of the two-step cluster analysis. Then, the cut-off point for the scale was calculated using ROC analysis with the determined groups. Results: Of the participants included in the study, 82.4% were male. 49% were single. 7.2% of the participants were elementary school graduates, 26.2% were high school graduates, 56.3% had a bachelor’s degree and 10.3% had a master’s degree. In the two-step cluster analysis, the data were divided into 3 clusters. The first cluster contained 17.5% of the data, the second cluster contained 34.8% of the data, and the third cluster contained 47.7% of the data. Individuals with a total scale score of 52.5 and above constituted 3.7% of all participants. The Cronbach’s Alpha value of the scale was found as 0,915. Conclusion: Among problematic cryptocurrency traders, individuals who exhibit gambling-like behavior are considered to be in the risk group. The problematic cryptocurrency trading scale was developed to measure this behavior. The rate of participants exhibiting risky behavior is a remarkable rate of 3.7%. The cut-off point for the Problematic Cryptocurrency Trading Scale was determined as 34.5.